Applying "design thinking" as a method for teaching in media education - Lugmayr, Artur (2011)
Design Thinking is a method for creative thinking and fostering idea development. This method has been selected as part of a university course to stimulate students in the creation of new ideas in the field of media industries. This paper describes the practical arrangements for organizing a Design Thinking course in a university context. It presents a hands-on guideline for conducting a similar course in an university setting on the basis of the "Frontiers of Media Management" course that has been organized by the EMMi Lab., at the Tampere Universy of Technology. © 2011 Author.